The Influence of Prior Language Experience on Foreign Language Anxiety: A Study on a Russian-Speaking Sample - Asiia Erzhanova; Anatoliy V. Kharkhurin (Peoples' Friendship University of Russia (RUDN University), 2022)
The topic of foreign language anxiety has attracted considerable attention in the scientific community in recent years. However, there is no universal approach to how to overcome foreign language anxiety. Apart from everything else, it creates barriers and prevents foreign language learners from achieving high results. The purpose of this study is to determine the impact of prior experience of learning foreign languages on language anxiety. The study sample consisted of 152 Russian-speaking persons aged 16-45 who were surveyed using the Foreign Language Classroom Anxiety Scale to evaluate communication apprehension, fear of negative evaluation and test anxiety. The participants also answered questions regarding their language learning experiences: about the number of acquired languages, the age of their acquisition and the level of proficiency in these languages. The MANCOVA results showed that the group with the similar language experience had lower levels of fear of negative evaluation ( F (1, 156) = 4.07, .05, η2 = .06). Based on the results of the study, the authors put forward several practical recommendations: firstly, it is advisable for the teacher to be aware of the student's prior language experience; secondly, it is proposed, in the educational process, to focus on the similarities in the phonology of the languages being studied; and, thirdly, it is also useful to pay extra attention to common morphemes in different languages.